Intra-European Trade of Manufacturing Goods: An Extension of the Gravity Model - Mark Vancauteren; Daniel Weiserbs (International Econometric Review (IER), 2011)
In this paper, we propose and test several extensions of the standard gravity model. This yields a specification that allows for (i) a more flexible income response; (ii) a competitiveness effect with a general and a specific component; and (iii) an alternative and consistent measure of remoteness. Those extensions were found to be significant factors to explain intra-EU trade. Next, we analyze the effect of EU harmonization of technical regulations on domestic and intra-EU trade. We find, at different levels of aggregation of the manufacturing sector, that harmonization of regulations has contributed to more intra-EU trade but, apparently, did not affect the so called border effect.
Keywords: F11; F14; F15; 330; Trade; EU Countries; Gravity Equation; Border Effects